Numerical analysis of repaired wall loss defect pipelines for optimum composite wrap thickness - M. Khaisem; S. Budhe; S. de Barros; M.D. Banea; N. R. F. Rohem (Fracture and Structural Integrity)
This paper presents the numerical analysis of failure pressure of wall loss defect metallic pipelines and validate it with experimental results. An optimization study is carried out using developed numerical model to propose the optimum composite repair thickness for cost effective repair system. A nonlinear explicit FE code with constitutive models for metallic steel and composite material to failure modelling was used. Three different cases: non-defective pipe, wall loss defective pipe and composite repaired of defective pipe are considered. It was found that the numerical results are in good agreement with the analytical results in all the three cases. Numerical results of composite repaired pipe were verified with hydrostatic test and both failure pressure and failure location closely matches, however the failure pressure determined by standard ISO/TS 24817 is too conservative for the same repair system. The optimization results revealed that even with reducing 40% of composite thickness with respect to the ISO/TS24817 standard, the repair system can sustain the designed failure pressure. The comparison showed that the standard ISO/TS 24817 provide an excessive composite repair thickness, which leads to increase the repair costs. Therefore, there is a scope for optimum composite repair thickness for cost effective repair system.